Effectiveness of the Interventional Program on Nurses’ Practices about Enteral Feeding Tube for Premature Neonates in the Neonatal Intensive Care Unit - Heyam Adnan Jabbar, Khatam M. Hattab, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nurses who are members of the health-care team are responsible for monitoring the dietary requirements of babies. Those who care for newborns in neonatal intensive care units (NICUs) must be well-versed in nutrition and feeding techniques, and they must follow scientifically verified recommendations when doing their duties. Objective: This aims to evaluate the effectiveness of the interventional program on nurses’ practices about enteral feeding tube for premature neonates in the neonatal intensive care unit. Methodology: A quasi-experimental design using test-retest approach for study group and control group participants employed in Kirkuk City Hospitals being, evaluated in three periods pre-test, post-test-1, and post-test-2. The interventional program being delivered as classroom lectures for participant. Data collection is done by self-administrated questionnaire form, and it was given for nurses to answer after taking their agreement. A non - probability purposive sample selected from nurses who were working at the neonatal intensive care units. The sample was forty nurses, (20) nurses enrolled as a control group and (20) nurses enrolled as a study group. The study group participants were exposed to an interventional program. The selection criteria included Only neonatal nurses’ who have from (1-20 and more) years of experience in the neonatal intensive care unit. Results: The findings in this table indicated that there is improvement in the nurses practice related to the insertion of the enteral feeding tube for the premature neonates and initiating continuous enteral feeding in the 1st period of (pretest and Posttest I) than (study group) in the 2nd period (pretest and posttest II) in item (number 1) by suggested sign score of assessment through the relative sufficiency. Conclusion: The interventional program demonstrated a favorite effect on nurses’ practice regarding the insertion of enteral feeding tubes and initiation continuous enteral feeding tube for the premature neonates.